Exploring the boundaries of landscape architecture - Bell, Simon; Herlin, Ingrid Sarlov; Stiles, Richard (New York, NY : Routledge, 2012)
"What insights can an anthropologist gain from the day-to-day use of parks? How does an economist view the supply and demand of an outdoor space? Why would an architect divide landscape into 'cultural' and 'natural' elements? Experts from around the world give their thoughts on how disciplines outside landscape architecture view the profession. Their insights link together theories from outside the area, giving constructive feedback on the lessons they gain from work in the environment and what they can contribute back to the subject. The book is an important addition to the literature on landscape architecture and provides a valuable companion to landscape theory modules for undergraduate and postgraduate students"--
boek
Keywords: Landscape architecture